DNA nanotechnology approaches for microRNA detection and diagnosis. Issue 20 (9th July 2019) - Chandrasekaran, Arun Richard; Punnoose, Jibin Abraham; Zhou, Lifeng; Dey, Paromita; Dey, Bijan K; Halvorsen, Ken
Abstract: MicroRNAs are involved in the crucial processes of development and diseases and have emerged as a new class of biomarkers. The field of DNA nanotechnology has shown great promise in the creation of novel microRNA biosensors that have utility in lab-based biosensing and potential for disease diagnostics. In this Survey and Summary, we explore and review DNA nanotechnology approaches for microRNA detection, surveying the literature for microRNA detection in three main areas of DNA nanostructures: DNA tetrahedra, DNA origami, and DNA devices and motifs. We take a critical look at the reviewed approaches, advantages and disadvantages of these methods in general, and a critical comparison of specific approaches. We conclude with a brief outlook on the future of DNA nanotechnology in biosensing for microRNA and beyond.